2020
DOI: 10.1002/anie.202000992
|View full text |Cite
|
Sign up to set email alerts
|

Modular Synthesis of Nona‐Decasaccharide Motif from Psidium guajava Polysaccharides: Orthogonal One‐Pot Glycosylation Strategy

Abstract: The synthesis of long, branched, and complex carbohydrate sequences remains a challenging task in chemical synthesis. Reported here is an efficient and modular one‐pot synthesis of a nona‐decasaccharide and shorter sequences from Psidium guajava polysaccharides, which have the potent α‐glucosidase inhibitory activity. The synthetic strategy features: 1) several one‐pot glycosylation reactions on the basis of N‐phenyltrifluoroacetimidate (PTFAI) and Yu glycosylation to streamline the chemical synthesis of oligo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Finally, removal of two DTBS groups in 26 with 70 % HF‐Py, deprotection of four Bz groups and the Lev group with NaOMe in MeOH, and global hydrogenolysis of 26 benzyl groups and 1 Cbz group with 10 % Pd/C completed the synthesis of undecasaccharide 1 in 49 % overall yield over three steps. It is noteworthy that orthogonal one‐pot synthesis of 1 – 2 based on glycosyl ABz and glycosyl PVB avoids the issues including aglycone‐transfer, undesired interferences of the departing species and unpleasant odor inherent to thioglycosides‐based orthogonal one‐pot glycosylation [16, 39] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, removal of two DTBS groups in 26 with 70 % HF‐Py, deprotection of four Bz groups and the Lev group with NaOMe in MeOH, and global hydrogenolysis of 26 benzyl groups and 1 Cbz group with 10 % Pd/C completed the synthesis of undecasaccharide 1 in 49 % overall yield over three steps. It is noteworthy that orthogonal one‐pot synthesis of 1 – 2 based on glycosyl ABz and glycosyl PVB avoids the issues including aglycone‐transfer, undesired interferences of the departing species and unpleasant odor inherent to thioglycosides‐based orthogonal one‐pot glycosylation [16, 39] …”
Section: Resultsmentioning
confidence: 99%
“…The major challenges are regio‐ and stereochemical problems during carbohydrates synthesis, which lead to a tedious and time‐consuming process for glycans synthesis [8, 9] . Indeed, examples of the synthesis of long, branched and complex carbohydrates containing multiple 1,2‐ cis glycosidic linkages with over 10 units are still limited [10–16] . Therefore, the development of efficient strategies for the assembly of long, branched and complex glycans with multiple 1,2‐ cis glycosidic bonds is highly desirable and remains one of formidable challenges in chemical synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical synthesis of both glycans and nucleosides is an effective, reliable and scalable method to solve the issues of the attainability, which can highly facilitate the development of new therapeutic agents and the decipherment of their functions. 3–11 During the past three decades, many strategies including automated chemical synthesis, 12 one-pot glycosylation strategies, 13 orthogonal glycosylation 14 and latent-active synthesis 15 have been developed to achieve the efficient construction of glycosidic bonds (C–O bonds), among which one-pot glycosylation strategies are highly efficient and attractive. In comparison with traditional glycosylation methods, which need tedious deprotection and protection manipulations during glycan assembly, one-pot glycosylation strategies not only avoid the purifications of intermediates and workups of the glycosylation interval, but also highly accelerate glycan synthesis and reduce chemical wastes.…”
Section: Introductionmentioning
confidence: 99%
“…However, one-pot glycosylation strategies for nucleoside synthesis (C–N bonds) are much less investigated. The development of one-pot glycosylation strategies suitable for both glycan and nucleoside synthesis remain poor and challenging due to the stereo- and regiochemical issues during glycan assembly, 13,16 together with other problems including the poor solubility and nucleophilicity of nucleobases in nucleoside synthesis. 3,11 …”
Section: Introductionmentioning
confidence: 99%
“…(family: Myrtaceae) is an evergreen shrub native to South America and has been widely cultivated in the tropical and subtropical regions of European, Africa, and Southeast Asia [ 8 ]. The dried PGL, with the functions of drying dampness, invigorating the spleen, clearing heat, and detoxifying, have been used for centuries as a folk Chinese medicine to treat diabetes, diarrhea, ulcers, and rheumatism [ 9 , 10 ]. Modern pharmacology studies have revealed the hypoglycemic efficacy and antidiabetic mechanism of PGL, involving increasing glycogen storage and reducing hormone-sensitive lipase activity, reducing the loss of insulin-positive β -cells and insulin secretion, and upregulating the mRNA expressions of IRS-1, phosphatidylinositol 3-kinase, and serine/threonine kinase protein B in livers of diabetic mice [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%